Do the retired elderly in Europe decumulate their wealth? The importance of bequest motives, precautionary saving, public pensions, and homeownership - Charles Horioka; Luigi Ventura (Osaka University, Institute of Social and Economic Research (ISER), 2022)
In this paper, we use micro data on a large number of European countries from the Survey of Health, Ageing and Retirement in Europe (SHARE) to examine the wealth accumulation (saving) behavior of the retired elderly in Europe. To summarize our main findings, we find that less than half of the retired elderly in Europe are decumulating their wealth and that the average wealth accumulation rate of the retired elderly in Europe is positive though relatively moderate (6.6% over a 3-year period). These findings strongly suggest that the Wealth Decumulation (or Retirement Saving) Puzzle (the tendency of the retired elderly to not decumulate their wealth or to decumulate their wealth more slowly than expected) applies in the case of Europe. Moreover, our regression results suggest that bequest motives, generous public pension systems, and the reluctance of retired elderly homeowners to sell or borrow against their owner-occupied housing are the primary explanations for the existence of the Wealth Decumulation Puzzle in Europe. Journal of Economic Literature classification numbers: D14, D15, D64, E21, H55, J14 Keywords: Aged, bequests, bequest intentions, bequest motives, dissaving, elderly, Europe, household saving, inheritances, intergenerational transfers, life cycle model or hypothesis, precautionary saving, retired elderly, Retirement Saving Puzzle, saving, SHARE, wealth accumulation, wealth decumulation, Wealth Decumulation Puzzle
Keywords: 330